THE PRELIMINARY PHYTOCHEMICAL SCREENING OF VARIOUS LEAf EXTRACTS OF PLANT Limonia acidissima Linn. - S. S. Shirankar; S. G. Dongre; R. P. Limsay; A. P. Somkuwar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The plant Limonia acidissima belongs to family Rutaceae. Various parts of this plant like fruit, seed, rind, bark, leaves and roots are being used to treat human and animal ailments. The fruits of the plant are most essential therapeutic portion containing bioactive molecules. This study is intended to reveal presence of some phytoconstituents from leaf extracts and review it thoroughly in order to validate its medicinal use. In the study it was found that aqueous and ethanolic extracts revealed maximum types of phytochemical classes as compared to acetone and petroleum ether extract which can be used for treatment with reference to its mentioned use. Many phytochemicals namely alkaloids, carbohydrates, glycosides, proteins, saponins, phenols, resins, etc. were detected which  reflects its therapeutic value.